The noise manual. - Berger, Elliott H. (American Industrial Hygiene Association, 2003)
This leading noise resource is specifically written for those with a technical interest in noise and for anyone who desires an improved general understanding of the subject. It addresses noise-related issues within the workplace and those arising in the community. Topics include: room noise criteria; speech and signal detection; community noise of hearing loss due to the noise exposure; prediction; and standards and regulations. Each of its 18 chapters have been peer-reviewed and contain numerous citations to the current literature, complemented by the expansive appendix on references for good practice.